MHD FLOW OF FLUID-PARTICLE SUSPENSION OVER AN IMPERMEABLE SURFACE THROUGH A POROUS MEDIUM OVER AN INCLINED STRETCHING SHEET - Murthy, ChannaKeshava; P.T., Manjuatha; L, Lokesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The analysis has been carried out to study the flow of dusty fluid over an inclined stretching sheet in a porous medium, where the flow is generated due to linear stretching sheet and influenced by uniform magnetic field. The governing partial differential equations for the flow are transformed into coupled non-linear ordinary differential equations using the suitable similarity transformation. The resultant system of ordinary differential equations is then solved numerically using Runge-kuttaFehlberg fourth- fifth method. The effects of different flow parameters like fluid-particle interaction parameter, magnetic parameter, permeability parameter, Prandtl number and Eckert number on the velocity are computed and presented graphically.